High-intensity interval training improves VO(2peak), maximal lactate accumulation, time trial and competition performance in 9–11-year-old swimmers - Sperlich, Billy (Springer-Verlag, 2010)
Training volume in swimming is usually very high when compared to the relatively short competition time. High-intensity interval training (HIIT) has been demonstrated to improve performance in a relatively short training period. The main purpose of the present study was to examine the effects of a 5-week HIIT versus high-volume training (HVT) in 9–11-year-old swimmers on competition performance, 100 and 2,000 m time (T (100 m) and T (2,000 m)), VO(2peak) and rate of maximal lactate accumulation (Lac(max)). In a 5-week crossover study, 26 competitive swimmers with a mean (SD) age of 11.5 ± 1.4 years performed a training period of HIIT and HVT. Competition (P < 0.01; effect size = 0.48) and T (2,000 m) (P = 0.04; effect size = 0.21) performance increased following HIIT. No changes were found in T (100 m) (P = 0.20). Lac(max) increased following HIIT (P < 0.01; effect size = 0.43) and decreased after HVT (P < 0.01; effect size = 0.51). VO(2peak) increased following both interventions (P < 0.05; effect sizes = 0.46–0.57). The increases in competition performance, T (2,000 m), Lac(max) and VO(2peak) following HIIT were achieved in significantly less training time (~2 h/week).